A Comparative Analysis of Bark and Leaf Essential Oil and their Chemical Composition, Antioxidant, Anti-inflammatory, Antimicrobial Activities and Genotoxicity of North East Indian Cinnamomum zeylanicum Blume - Gogoi, Roktim; Sarma, Neelav; Loying, Rikraj; Pandey, Sudin K.; Begum, Twahira; Lal, Mohan (Natural Products Journal, The, 2021)
Background: Cinnamomum zeylanicum Blume ( Lauraceae) bark and leaf essential oil possesses eugenol as the major component. Both the essential oils have the potential antioxidant, anti- inflammatory, antimicrobial and negligible genotoxicity. Objective: A comparative chemical composition and biological evaluation of Cinnamomum zeylanicum Blume, bark and leaf essential oils, originated from North-East India has been investigated in the present study. Methods: Gas chromatography/mass spectroscopy analysis was used to investigate the chemical composition of the essential oil samples. DPPH free radical scavenging activity, and reducing power assay were used for antioxidant activity evaluation. Similarly, egg albumin denaturation assay, protease inhibitory activities were used for anti-inflammatory activity, while genotoxicity was evaluated by using Allium cepa assay and antimicrobial activities using disc diffusion and minimum inhibitory concentration assay. Results: The GC/MS results showed that eugenol is the major component of C. zeylanicum bark (84.48%) and leaf (48.78 %) essential oil. Significant antioxidant activity was observed for both essential oils in the DPPH free radical scavenging assay (IC50= 103.2 μg/mL, bark; IC50= 234.7 μg/mL, leaf), and reducing power assay (absorbance of 1.802 nm, 0.907 nm in 48 μg/mL for bark and leaf essential oil respectively). In-vitro anti-inflammatory activity revealed strong potential of leaf essential oil (protein denaturation assay, IC50= 0.05279 μg/mL; protease inhibitory activity IC50= 3.607 μg/mL) in comparison to bark essential oil (protein denaturation assay IC50= 0.1491, protease inhibitory activity IC50= 61.06). Allium cepa root growth test, mitotic index, and chromosomal aberration test were performed to investigate the genotoxicity of C. zeylanicum bark and leaf essential oil, which resulted in no toxic nature of both the essential oils. Antimicrobial activity against eight bacterial and fungal strains revealed good antimicrobial properties with the MIC value of Staphylococcus aureus at 5 μL/mL (bark), Aspergillus niger at 2.5 μL/mL (bark); Bacillus cereus at 5 μL/mL (leaf) and Aspergillus niger at 2.5 μL/mL (leaf). Conclusion: Collectively, these findings indicated the strong biological potential of both essential oils, although bark essential possesses better biological activities than the leaf essential oil and could be used in the food and beverage industries.
Keywords: genotoxicity